Uso do ácido orgânico (ácido fumárico) nas rações de frangos de corte - Runho, R. C.; Sakomura, N. K.; Kuana, S.; Banzatto, D.; Junqueira, O. M.; Stringhini, J. H. (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 1997)
This experiment was carried out to evaluate the effect of the addition of fumaric acid to broiler diet on birds performance. One thousand and eighty Hubbard day-old broiler chicks were alloted in a randomized block design, six treatments with two replicates of males, and four replicates of females. Three basal diets were formulated to meet the nutritional requirements in each growing phase: from 1 to 21 days, 21 to 37 days and 37 to 45 days. Treatments consisted first in the addition of growth promoter to 0.75 and 1.0%, of fumaric acid. The group treated without of both growth promoter and fumaric acid presented a higher intake and a smaller feed:gain ratio in relation to the fumaric acid treated groups. However, there were no differences among groups treated with growth promoter and fumaric acid. The contrasts did not show any difference among weight gain, carcass yield and abdominal fat. The addition of fumaric acid levels to the diets promoted reduction of feed intake, without any effect on weight gain, improving, therefore, the feed/gain ratio. A digestibility experiment was carried out, using 30 Hy-Line roosters, to determine apparent metabolyzed energy (AME), corrected by nitrogen of the diets containing 0.0, 0.5 and 1.0% of the acid. An increase on the AME of the diets was observed with fumaric acid addition.
Use of an organic acid (fumaric acid) in broiler rations
Keywords: fumaric acid; broilers